Machine translation outputs in Spanish–Chinese legal translation: comparisons of different legal genres and domestic vs. non-domestic systems, error analysis and implications for post-editing - Feng, Hongxia (Revista de llengua i dret, 2025)
Although some studies have discussed the role of machine translation (MT) systems in legal texts, very few have addressed the Spanish–Chinese language pair. This article compares the outputs of Spanish legal texts of different genres translated into Chinese using various MT systems such as DeepL Translator, Google Translator, GPT-4, Baidu Translator, Youdao Translator, and Tencent Translator. The aim is to identify whether there is a quality difference between Chinese domestic and non-domestic MT systems and to investigate whether MT raw outputs for legal texts across different genres exhibit distinct types of translation error. Three types of Spanish legal text were selected for analysis: an administrative approval authorisation, a maritime judgement, and a legislative text. The target texts produced by the six MT systems were evaluated using automated metrics as well as human evaluations focusing on adequacy and fluency. Additionally, the present paper follows the framework of the Dynamic Quality Framework (DQF) and the Multidimensional Quality Metrics (MQM) typology for MT, as proposed by Lommel and Melby (2018), to categorise and analyse different error types. Based on this analysis, translation strategies for post-editing (PE) are proposed. Si bé existeixen estudis que han abordat el paper dels sistemes de traducció automàtica (TA) en textos jurídics, molt pocs han tractat la combinació lingüística castellà-xinès. Aquest article compara els resultats de diverses tipologies de textos jurídics traduïts del castellà al xinès mitjançant sistemes de TA, com ara DeepL Translator, Google Translator, GPT-4, Baidu Translator, Youdao Translator i Tencent Translator. L’objectiu és detectar si hi ha diferències qualitatives entre els sistemes de TA nacionals xinesos i els no nacionals, així com analitzar si els resultats inicials de TA en diferents tipus de textos jurídics presenten errors de traducció diferenciats. Per a l’estudi s’han seleccionat tres tipus de textos jurídics en castellà: una autorització administrativa, una sentència marítima i un text legislatiu. Els textos meta produïts pels sis sistemes de TA s’han avaluat amb mètriques automatitzades i valoracions humanes basades en la seva adequació i fluïdesa. D’altra banda, aquest article segueix el marc del Dynamic Quality Framework (DQF) i el Multidimensional Quality Metrics (MQM) per a la TA, tal com proposen Lommel i Melby (2018), per categoritzar i analitzar les diferents tipologies d’error. A partir d’aquesta anàlisi, proposa estratègies de traducció per a la postedició (PE). Si bien existen estudios que han abordado el papel de los sistemas de traducción automática (TA) en textos jurídicos, muy pocos han tratado la combinación lingüística castellano-chino. Este artículo compara los resultados de varias tipologías de textos jurídicos traducidos del castellano al chino mediante sistemas de TA, como DeepL Translator, Google Translator, GPT-4, Baidu Translator, Youdao Translator y Tencent Translator. El objetivo es detectar si existen diferencias cualitativas entre los sistemas de TA nacionales chinos y los no nacionales, así como analizar si los resultados iniciales de TA en diferentes tipos de textos jurídicos presentan errores de traducción diferenciados. Para el estudio se han seleccionado tres tipos de textos jurídicos en castellano: una autorización administrativa, una sentencia marítima y un texto legislativo. Los textos meta producidos por los seis sistemas de TA se han evaluado con métricas automatizadas y valoraciones humanas basadas en su adecuación y fluidez. Por otro lado, este artículo sigue el marco del Dynamic Quality Framework (DQF) y el Multidimensional Quality Metrics (MQM) para la TA, tal y como proponen Lommel y Melby (2018), para categorizar y analizar las diferentes tipologías de error. A partir de este análisis, propone estrategias de traducción para la post-edición (PE).